Hydrophilic Versus Lipophilic Statin Treatments in Patients With Renal Impairment After Acute Myocardial Infarction - Min Hye Kang; Weon Kim; Jin Sug Kim; Kyung Hwan Jeong; Myung Ho Jeong; Jin‐Yong Hwang; Seung Ho Hur; Hyeon Seok Hwang (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Hydrophilic and lipophilic statins have similar efficacies in treating coronary artery disease. However, specific factors relevant to renal impairment and different arterial pathogeneses could modify the clinical effects of statin lipophilicity, and create differences in protective effects between statin types in patients with renal impairment. Methods and Results A total of 2062 patients with acute myocardial infarction with an estimated glomerular filtration rate <60 mL/min per 1.73 m2 were enrolled from the Korea Acute Myocardial Infarction Registry between November 2011 and December 2015. The primary end point was a composite of 2‐year major adverse cardiac and cerebrovascular events (MACEs) after acute myocardial infarction occurrence. MACEs were defined as all‐cause death, recurrent myocardial infarction, revascularization, and stroke. Propensity‐score matching and Cox proportional hazards regression were performed. A total of 529 patients treated with hydrophilic statins were matched to 529 patients treated with lipophilic statins. There was no difference in the statin equivalent dose between the 2 statin groups. The cumulative event rate of MACEs, all‐cause mortality, and recurrent myocardial infarction were significantly lower in patients treated with hydrophilic statins in the propensity‐score matched population (all P<0.05). In the multivariable Cox regression analysis, patients treated with hydrophilic statins had a lower risk for composite MACEs (hazard ratio [HR], 0.70 [95% CI, 0.55–0.90]), all‐cause mortality (HR, 0.67 [95% CI, 0.49–0.93]), and recurrent myocardial infarction (HR, 0.40 [95% CI, 0.21–0.73]), but not for revascularization and ischemic stroke. Conclusions Hydrophilic statin treatment was associated with lower risk of MACEs and all‐cause mortality than lipophilic statin in a propensity‐score matched observational cohort of patients with renal impairment following acute myocardial infarction.